Rebellion and Miracles on the Welsh March: Accounts in the Miracle Collection of St Thomas de Cantilupe. (1st December 2019) - Bass, Ian Luke
It has recently been argued that some of the miracles performed between 1287 and 1312 by St Thomas de Cantilupe, bishop of Hereford (1275–82, canonized 1320), can be seen as an imprinting of 'cultural imperialism' on the recently conquered Welsh. What this argument has not considered, however, are the miracles recorded for other English and Welsh recipients involved in various Anglo-Welsh conflicts from 1287 onwards. This article offers a revision of this assessment by considering the wider setting of the Cantilupe cult, examining the other Welsh miracle recipients and placing them in the context of Anglo-Welsh conflict in the March.